TINDAK PIDANA PENGGELAPAN KARENA HUBUNGAN KERJA SECARA BERSAMA-SAMA (PUTUSAN NO 3557/PID.B/2021/PN MDN) : Crime of Embezzlement Due to Collaborative Employment Relationships (Decision No. 3557/PID.B/2021/PN MDN) - Gusti Muhammad Reza Meldianta Rahman; Eriyantouw Wahid (Reformasi Hukum Trisakti, 2024)
The economic conditions that are being impacted by Covid 19 are one factor in the occurrence of criminal acts of embezzlement. In criminal acts, embezzlement often occurs because of a joint work relationship. At trials it is often found that perpetrators of embezzlement due to work relationships are subject to ordinary embezzlement crimes, as is the case with decision No. 3557/PID.B/2021/PN MDN. The issues raised are 1) are the actions of the perpetrator of the crime of embezzlement due to a joint work relationship appropriate based on Article 372 of the Criminal Code? (Study Decision Number 3557/Pid.B/2021/PN Mdn) and 2) how do perpetrators jointly commit the crime of embezzlement due to work relationships? (Study Decision Number 3557/Pid.B/2021/PN Mdn). The normative juridical used in this research is descriptive analytical in nature. The use of secondary data then uses qualitative analysis which is drawn logically deductively in drawing conclusions. The result is: 1) It is not appropriate to use Article 372 of the Criminal Code in this case, 2) Taking part is a form of participation in this case. In conclusion, this criminal act is included in embezzlement under Article 374 of the Criminal Code.